177k views
1 vote
How do you find the sum of cube ?

How do you find the sum of cube ?-example-1

1 Answer

3 votes

Answer:


(2x+5)(4x^(2) -10x+25)=0

Explanation:

Given:

The given equation is.


8x^(3) +125=0

Find the some of cube.

Solution:


8x^(3) +125=0


2^(3)x^(3) +5^(3)=0


(2x)^(3) +5^(3)=0----------(1)

The sum of the cube formula is given below.


(a^(3) +b^(3))=(a+b)(a^(2) -ab+b^(2) )-----------(2)

By comparing equation 1 and equation 2


a=2x, b=5

substitute a and b value in equation 2


((2x)^(3) +5^(3))=(2x+5)((2x)^(2) -(2x)(5)+5^(2))


((2x)^(3) +5^(3))=(2x+5)(4x^(2) -(10x)+25)


((2x)^(3) +5^(3))=(2x+5)(4x^(2) -10x+25)

Therefore the sum of the cube
(2x+5)(4x^(2) -10x+25)=0

User Dave Loepr
by
4.8k points